Steady-state distributions of nascent RNA for general initiation mechanisms - Juraj Szavits-Nossan; Ramon Grima (Physical Review Research, 2023)
Fluctuations in the number of nascent RNA accurately reflect transcriptional activity. However, mathematical models predicting their distributions are difficult to solve analytically due to their non-Markovian nature stemming from transcriptional elongation. Here we circumvent this problem by deriving an exact relationship between the steady-state distribution of nascent RNA and the distribution of initiation times, which can be computed for any general initiation mechanism described by a set of first-order reactions. We test our theory using simulations and live cell imaging data.